Optimization of Salary System Application for Financial Department Performance Efficiency - Rahayu, Sri; Budiarto, Mukti; Malika, Najalia (UNIVERSITAS RAHARJA, 2025)
Rapid advancements in technology compel individuals and organizations to adapt to the ongoing shifts. One significant example of technological advancement is the increasing adoption of computerized work systems across various companies. PT Aliansi Global Manufaktur, a local shoe manufacturing company, is currently navigating this technological shift. The study originates from the company’s reliance on a manual payroll data management system. Such a manual approach presents several challenges, including susceptibility to errors, time and energy inefficiencies in data processing, and extensive storage space requirements. This study utilizes the PIECES analysis framework, which evaluates aspects such as Performance, Information, Economy, Control, Efficiency, and Service. For the design phase, it employs Unified Modeling Language (UML) alongside PHP programming with the Codeigniter framework for system development and a database for data storage. A proposed solution to address these challenges is the development of a web-based payroll system, aimed at reducing errors in salary calculations and simplifying the payroll process.